Scopping review: use of biofertilizers and humic substances in Phaseolus vulgaris (Fabaceae) for dry zones - Aguirre-Pérez, Laura-Liliam; Suárez-Fragozo, Elva-Cecilia; Arias-Sarabia, Geider-Eduardo; Tofiño-Rivera, Adriana-Patricia; Cubillos-Hinojosa, Juan-Guillermo (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2023)
The common bean crop in dry areas is affected by the climate change and the low availability of nutrients that limits its yield. The objective of this review was to analyze the scope of the scientific literature on the use of inoculants based on Plant growth promoting rhizobacteria (PGPR) and humic substances (HS) in sustainable agronomic management of common bean crop and drought tolerance, for the generation of recommendations applicable to the production cultivation in dry areas from low tropic. An exploratory review on the use of PGPR and SH in common bean was carried out, since the first publications until December 2022 in the databases: Science direct, SciElo, SpringerLink, Scopus, Pubmed and Proquest. The co-inoculation of rhizobia with other PGPR was the most frequent technique in the reviewed articles. However, the combined application with SH allows greater tolerance to the water stress caused by drought. Rhizobia species most reported as efficient were Rhizobium tropici, Rhizobium etli and the strain CIAT 899 (R. tropici). In addition, the strain CIAT 899 was found to be the most useful in inoculant formulations for common beans under drought conditions in Brazil. In Colombia, only one registered product based on Rhizobium phaseoli was found for common bean, although there are no reports of evaluation of this strain under drought stress conditions.